Pizza and Hamburger Consumption to Overweight among Adolescents in Jambi City - Kalsum, Ummi; Nainggolan, Sahridayanti; Ng, Nawi (UI Scholars Hub, 2018)
Junk food is unhealthy and poor in nutrient quality, and may result in weight gain, obesity, and coronary heart disease, if consumed regularly. The prevalence of overweight in adolescents is 5-10% higher in urban areas. Adolescents undergo lifestyle changes, including in food consumption behavior. This study aimed to determine relation between junk food consumption patterns and overweight in adolescents. This study was conducted based on a cross-sectional design. A total of 137 high school students in Jambi City were involved in this study. Patterns of junk food consumption were assessed using food frequency questionnaires that examined the eating habits of study subjects. The variables were sex, maternal education, parents’s occupation, and family’s socio-economic level. Analysis was conducted using the chi-square test and multiple logistic regression. Nutritional status was measured using body mass index-forage with WHO Antro software. The results of this study indicated a 23.4% prevalence of overweight in adolescents. After controlling for maternal education, father’s occupation, instant noodle eating habits, and tea, coffee and cookies consumption, final model showed that consumption of pizza and hamburgers among adolescents was the dominant determinant for overweight (OR=3.55). Consumption of pizza and hamburger was related to overweight among adolescents in Jambi City.